MPLEMENTASI PENGENDALIAN KUALITAS DENGAN METODE STATISTIK PADA PABRIK SPAREPARTS CV VICTORY METALLURGY SIDOARJO - Santoni Darmawan Tanjong (CALYPTRA, 2013)
Spareparts industry is an industry with good prospects today, so it can generate a very large profit. The fact is the growing sales of motorcycles in 2012. Quality is a very important factor for the survival of the company. Consumers will evaluate the quality of a company based on the quality of the goods or services offered. So we can say that the products or services provided to the consumer is a reflection of the company itself. Because this study was done to implement the method for quality control in "Victory CV Metallurgy" to improve the quality of their products. Statistical tools used in this study are: Check Sheet, Pareto Diagram, Cause and Effect Diagram, Full Map and Table FMEA (Failure Mode Effect Analysis). The results showed that there are still defects in the brake pedal, the rear footstep, and handlebar steer the company exceeds tolerance limits. Pareto diagrams are used to determine the number of defects that affect the company's production process. The production process is well within control. Then made a causal diagram to determine the actual root of the problem and the root note of the most prominent issues in human resources. After that "CV Victory Metallurgy" using Failure Mode Effect Analysis to address the disability that occurs with prioritizing repairs